The Influence of Digital Payment Adoption on Microenterprise Profitability in Yogyakarta - Abdullah Munafri (Mustard Journal De Ecobusin, 2025)
This study analyzes the effect of digital payment adoption on the profitability of microenterprises in Yogyakarta. Microenterprises are vital to the local economy yet often encounter financial constraints that limit growth. The rise of digital payment platforms such as QRIS, GoPay, OVO, and Dana presents opportunities to enhance operational efficiency and market competitiveness. Using a quantitative explanatory research design, data were collected from 100 microenterprise owners selected through purposive sampling. Structured questionnaires and interviews were employed to obtain relevant information. Data were analyzed using descriptive statistics, validity and reliability testing, and multiple linear regression to examine the research hypothesis. Digital payment adoption was evaluated based on frequency, ease, security, and convenience, while profitability was measured through sales growth, profit margin, cost efficiency, and transaction volume. The results reveal that digital payment adoption significantly improves profitability, explaining 51.1% of its variance. The remaining 48.9% may be influenced by other unexamined factors. These findings highlight that digital payment systems play a crucial role in enhancing financial performance. Strengthening digital literacy and payment infrastructure is recommended to optimize financial technology adoption among microenterprises in Yogyakarta.